Sex differences in the risk profiles for anemia in people living with HIV, A cross sectional study - Kingsley Kamvuma; Benson M. Hamooya; Kaseya O. R. Chiyenu; Yusuf Uthman Ademola; Steward Mudenda; Alfred Machiko; Sepiso K. Masenga; Sody M. Munsaka (PLoS ONE, 2025)
Background Anemia in people living with HIV (PLWH) significantly impacts quality of life and health outcomes. This study aimed to determine sex differences in factors associated with anemia in PLWH at Livingstone University Teaching Hospital, Zambia. Methods This cross-sectional study involved 631 PLWH aged 18 years or older who had been on combinational ART for at least 6 months. Data was collected via standardized questionnaires and medical records. Anemia was defined as haemoglobin levels < 13 g/dL for men and < 12 g/dL for women, based on WHO criteria. Logistic regression models assessed the associated factors, stratified by sex. Results Participants had a median age of 44 years, with a female preponderance of 64.2%. The overall prevalence of anemia was 36%, significantly higher in females (41.1%) compared to males (27.2%) (p < 0.001). In females, waist circumference (AOR =  0.97, 95% CI: 0.95-0.99, P =  0.018), albumin levels (AOR =  0.96, 95% CI: 0.92-0.99, P =  0.047), NNRTI regimens (AOR =  2.78, 95% CI: 1.34-5.78, P =  0.006), microcytosis (AOR =  3.18, 95% CI: 1.26-8.03, P =  0.014), and hypertension (OR =  0.34, 95% CI: 0.13-0.87, P = 0.024) were linked to anemia in adjusted analysis but these associations were abrogated by male sex. Conclusions We found a 36% prevalence of anemia among PLWH, with a higher prevalence in females (41%) compared to males (27%), including severe forms of anemia. Among females, anemia was linked to lower waist circumference, lower albumin levels, NNRTI regimens, microcytosis, and blood pressure but not males. Further studies are warranted.